PENGGUNAAN EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) SEBAGAI DESINFEKTAN PADA DAYA TETAS DAN LAMA PENETASAN TELUR IKAN MAS (Cyprinus carpio L.) - Basri, Moh (AgriSains, 2012)
This research was aimed to know explore the content of crude protein, crude fiber, calsium and phosphore of diets consumed by anoa in protected forest between tahura and pangi binangga nature reserve. The anoa diets collected from protected forest between tahura and Pangi Binangga nature reserve. Proxymate analysis method was used to study crude protein, crude fiber, calsium and phosphore content of anoa diets. The analyze results of nutrients composition of Syzigium sp., Cordia mixab, Ficus miquelly, Ficus ampelas, Imperata cylindrica, Smilax leocophylla, Saccarum spontaneum, Paspalum conjugatum and Isachne globosa show that crude protein of 7,23-12%, crude fiber of 14,5-33,1%, calsium of 0.027-0,310% and phosphore of 0,09-0,15%. Key words: Anoa diets, nutrient composition, pangi binangga and tahura.